2018
DOI: 10.1016/j.foodhyd.2018.06.015
|View full text |Cite
|
Sign up to set email alerts
|

In vitro digestion of lactoferrin-glycomacropeptide nanohydrogels incorporating bioactive compounds: Effect of a chitosan coating

Abstract: The behaviour of lactoferrin (Lf)glycomacropeptide (GMP) nanohydrogels with and without a chitosan coating was evaluated during gastrointestinal digestion. The application of a chitosan coating allowed to reduce the protein degradation from 86% to 76% for Lf and from 71% to 53% for GMP. Protein bioaccessibility results showed that in nanohydrogels with chitosan coating 23% of Lf and 40% of GMP remained intact until absorption. Based on these results, the bioaccessibility of two different bioactive compounds en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 26 publications
(38 reference statements)
1
17
0
Order By: Relevance
“…5A). Bourbon et al (2018) observed a similar behaviour when using a dynamic in vitro GI model to determine the bioavailable fraction of caffeine (as hydrophilic model compound) using Lf-GMP nanohydrogels with chitosan coating as the encapsulation matrix. The authors obtained a caffeine bioavailability of 63.1 ± 0.2 % when caffeine was associated to nanohydrogels and of 59.2 ± 2.1 % when caffeine is present in its free form.…”
Section: Bioactive Model Compounds Bioaccessibility and Bioavailabilitymentioning
confidence: 59%
See 2 more Smart Citations
“…5A). Bourbon et al (2018) observed a similar behaviour when using a dynamic in vitro GI model to determine the bioavailable fraction of caffeine (as hydrophilic model compound) using Lf-GMP nanohydrogels with chitosan coating as the encapsulation matrix. The authors obtained a caffeine bioavailability of 63.1 ± 0.2 % when caffeine was associated to nanohydrogels and of 59.2 ± 2.1 % when caffeine is present in its free form.…”
Section: Bioactive Model Compounds Bioaccessibility and Bioavailabilitymentioning
confidence: 59%
“…Generally, food proteins are usually hydrolysed in the stomach environment (Zhang & Vardhanabhuti, 2014). Bourbon et al (2018) evaluated both lactoferrin (Lf) and glycomacropeptide (GMP) nanohydrogels hydrolysis using an in vitro dynamic GI model. These authors observed that at least 45 % of Lf and 70 % of GMP remain undigested after simulated gastric phase.…”
Section: β-Lg Micro-and Nanostructures Hydrolysis Degree During In VImentioning
confidence: 99%
See 1 more Smart Citation
“…These authors concluded that the chitosan layer improved the stability and bioaccessibility of active compounds during in vitro digestion. Furthermore, the degradation of the lipophilic compound was lower when compared with the system without the chitosan layer [99].…”
Section: Controlled Releasementioning
confidence: 99%
“…Some nutraceuticals, such as silymarin, curcumin, vitamin E, docosahexaenoic acid, choline and phosphatidylcholine are used in treating and preventing steatosis [15]. Additionally, many nutraceutical products, such as gallic acid, caffeine, curcumin and others act as anti-aging and antioxidant agents [16, 17]. PUFA-rich fish oils reduce the risk of coronary cardiovascular diseases and enhance the brain functions [18].…”
Section: Introductionmentioning
confidence: 99%